Deus ex machina - Rupčić, Tijana (Poligrafi, 2024)
The study of artificial intelligence (aI) and religion, particularly the concept of god within video games, is a rich field that explores how digital spaces can reflect and shape philosophical and theological discourses. Ever since their first introduc-tion to the public, video games have often been a unique medium for exploring complex narratives and are tied to the different expressions of religion and spiri-tuality. The integration of aI characters or deities into video games challenges the traditional understanding of divinity and intelligence. This article examines the imaginaries of aI and god in two video games, Ga-lerians (1999) and I Have No Mouth, and I Must Scream (1995), focusing on how these elements are used to construct narrative worlds and reflect cultural percep-tions of technology and the divine. In these games, the aI characters that gained consciousness started embodying god-like characteristics, such as omnipotence, omniscience, and omnipresence, raising questions about free will, predestination, and the nature of consciousness. These representations draw from existing religio-us traditions while also pushing the boundaries of theological thought, suggesting new interpretations of divinity in the context of advanced technology. The article will also closely examine the concepts of emotions that aIs in Galerians and I Have No Mouth, and I Must Scream “experience.”The author relies on a game-immanent approach through detailed analysis of the aforementioned games in order to explore how the imaginaries of aI and god converge, offering insights into the evolving relationship between humanity, te-chnology, and spirituality.
Keywords: artificial intelligence; duhovnost; Galerians; I have no mouth, and I must scream; spirituality; umetna inteligenca; videogames; videoigre